The Influence of Appraiser Competence, Appraiser Professional Education, and Technological Adaptability on Appraiser Career Development in the Digital Era at KJPP Firman Azis and Partners in West Java - Pratama, Ivaldy Chefa; Hidayat, Agi Syarif; Juwita, Juwita (IJEBD (International Journal of Entrepreneurship and Business Development), 2026)
Purpose: This study aims to analyse the influence of appraiser competence, professional appraisal education, and technological adaptability on career development in the era of digital transformation at KJPP Firman Azis dan Rekan. Design/methodology/approach: This research employs a quantitative approach with an explanatory research design. Primary data were collected through structured questionnaires using a Likert scale and analysed using multiple linear regression supported by classical assumption tests. Findings: The results indicate that appraiser competence and technological adaptability have a positive and significant effect on career development. Professional appraisal education also contributes positively, both partially and simultaneously. Research limitations/implications: This study is limited to a single public appraisal firm, which may restrict the generalisability of the findings to similar organisational contexts. Practical implications: The findings suggest that management should strengthen digital competencies and professional education programs to enhance sustainable career development in the digital era. Originality/value: This study integrates human capital theory and digital transformation perspectives within the context of the appraisal profession in Indonesia. Paper type: Research paper